Rekomendasi Desain Operasi Pelayanan Publik Melalui Evaluasi Pemenuhan Harapan Masyarakat dan Pengukuran Kinerja (Membidik Pelayanan Publik Negara China) - Yuli Harwani; Hesti Maheswari (Forum Manajemen Indonesia (FMI), 2014)
Complaints communities in the developing countries, especially Indonesia to the public service are still extremely high. Perceived imbalances such as in: obscurity of time, cost and method of service; discrimination in services based on the relationships of friends, family, political affiliation, ethnic and even religious; chain length the more entrenched bureaucracy and bribery and extortion. This condition is a signaled for the government to seek strategic solutions to improve public services. This study aims to discover the design of public service operations in accordance with the expectations of society by measuring the performance of the public service. Recommended design is a design that lead to e-Government and reinventing goverment to give birth standard operating procedures (SOP) and minimum service standards (SPM) for public services in Indonesia, especially in the public service that is closest to the village community with Quality function deployment (QFD) in house of quality (HOQ) method. In the first phase of the study mapped 36 public expectations of public services, which are shown in this analysis that the public is not getting an appropriate and satisfying service, although does not show the high gap. On the other hand mapping the public response to the internet-based administration showed the unpreparedness of the people against the internet-based public services. The majority of respondents claimed to feel more comfortable and definitely served in the village office immediately met with the officers. Queue and the possibility of intervention or extortion is not a problem for society. In the second phase of this study will examine the true public service bureaucracy and the possibility of cutting the bureaucratic process that is more streamlined, clear, fast, and facilitate community. Last step is to benchmark the Chinese State as densely populated countries such as Indonesia, to make strategic steps and implementable in problem solving public dissatisfaction with public services and the number of maladministration. Keywords: fulfillment of community expectations, e-goverment, reinventing goverment, standard operating procedures, minimum service standards, good governance